Long-term health-related quality of life in Kawasaki disease complicated with coronary artery aneurysm in the Nanjing region of China: Results of the largest single-center assessment - Wenting Gao,; Ying Meng,; Yu Chen,; Mei Chen, (Archives of Rheumatology, 2024)
Objectives: The study aimed to compare the long-term health-related quality of life in children with Kawasaki disease (KD) with and without coronary artery aneurysms (CAAs) in the largest pediatric medical center in the Nanjing region of China. Patients and methods: The retrospective study included a total of 107 patients (54 males, 53 females; mean age: 3.4±1.8 years; range, 2.12 to 1.75 years) between January 2012 and December 2022. Among these patients were a cohort of 64 child patients diagnosed with CAAs due to KD and a control group of 43 hospitalized child patients with KD without CAAs. The children with CAAs were divided into two groups according to the size of their aneurysms: the aneurysm group and the giant aneurysm group. Both child-reported and parent/proxy-reported Pediatric Quality of Life Inventory surveys were collected at baseline and during long-term follow-up. Results: The median follow-up duration was 5.58 years (range, 1.03 to 10.67 years). The mean age at the time of diagnosis was 3.43±1.75 years (range, 2.12 to 12.19 years). At baseline, children reported a total score of 48.63±16.60 and parents reported a mean score of 46.76±14.77 in the giant aneurysm group. The child-reported and parent/proxy-reported outcomes were 54.71±15.82 and 52.73±13.34 in the aneurysm group and 48.30±28.24 and 46.35±15.79 in the control group, respectively. In long-term follow-up, children in the aneurysm group reported a mean score of 81.61±19.50, which was 9.70 (95% confidence interval (CI): 2.22-17.18) points higher than that of the control group (p=0.014) and 9.51 (95% CI: 2.02-16.98) points lower than that of the giant aneurysm group (p=0.012). Similarly, parents reported a mean score of 81.03±12.57 in the aneurysm group, which was significantly lower than that of the control group (p=0.010) and significantly higher than that of the giant aneurysm group (p=0.009). Conclusion: A proportion of children presenting with CAAs without complete recovery often encountered issues that disrupted their well-being during long-term follow-up. Therefore, routine outpatient health-related quality of life screening might be set as an appropriate supportive service to assist in identifying patients with a history of CAAs to eliminate the risk for long-term disabilities following the initial clinical improvement.